Meneropong Relevansi Konsep Kebebasan Fichte Terhadap Pandangan Kebebasan dalam Etika Kontemporer: Examining the Relevance of Fichte's Concept of Freedom to the View of Freedom in Contemporary Ethics - Aja, Dominikus M.; Dedi S. Se, Eduardus; Righo, Isfridus Damasus; Naibina, Gualbertus A. (Undiksha, 2024)
Medieval philosophy is a system of philosophy that emphasizes the importance of the role of revelation in the field of science, thus trying to synthesize Christian theology with Greek philosophy. Such emphasis made many philosophers give birth to various dogmatic thoughts. Dogmatic thoughts always lead to the concept of human freedom as a false freedom and not absolute freedom so that life in accordance with determination is a good life while life otherwise is bad. The consequence of such thinking is the loss of human dignity as an autonomous and intelligent being. The false and dogmatic idea of freedom was strongly criticized and opposed by Fichte. Through his various thoughts in subjective idealism and ethics, Fichte emphasized that all humans are free and autonomous beings because they have consciousness and reason in themselves. As autonomous and intelligent beings, every human being can determine their lives freely without any coercion from outside themselves. In addition, human freedom according to Fichte is freedom that is responsible for others. This means that one's freedom of action should not violate the freedom of others because all humans have the same dignity. Fichte's thinking contradicts the contemporary concept of freedom, which is individualized and ignores social solidarity. This study uses qualitative descriptive analysis method by means of literature study in collecting both primary and secondary data on Fichte's philosophy and freedom thought.